2018
DOI: 10.1002/qre.2351
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel collapse risk assessment based on multistate fuzzy Bayesian networks

Abstract: Excessive structural deformation or collapse can lead to heavy casualties and substantial property loss. This paper presents a novel integrated risk assessment method based on multistate fuzzy Bayesian networks integrated with historical data, expert investigations, probability distribution calculations, discrepancy analysis, sensitivity analysis, and decision‐making. A new expert investigation is proposed with small probability intervals, expert weights, confidence index, etc. After gaining expert judgment by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 47 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…For example, Burke et al proposed a novel design selection strategy using multiple criteria with enhanced robustness of user priorities . Sun et al introduced a novel expert investigation with consideration of small probability intervals in order to assess the risk of tunnel collapse . A risk matrix is developed using an extension TOPSIS method and an intuitionistic fuzzy number by Yazdi to enhance the performance of a safety system in a refinery under construction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Burke et al proposed a novel design selection strategy using multiple criteria with enhanced robustness of user priorities . Sun et al introduced a novel expert investigation with consideration of small probability intervals in order to assess the risk of tunnel collapse . A risk matrix is developed using an extension TOPSIS method and an intuitionistic fuzzy number by Yazdi to enhance the performance of a safety system in a refinery under construction .…”
Section: Introductionmentioning
confidence: 99%
“…22 Sun et al introduced a novel expert investigation with consideration of small probability intervals in order to assess the risk of tunnel collapse. 23 A risk matrix is developed using an extension TOPSIS method and an intuitionistic fuzzy number by Yazdi to enhance the performance of a safety system in a refinery under construction. 3 In the group decision-making procedure, each expert is asked to express their opinions about which grade level (eg, possibility and priority) belongs to a specified factor (eg, alternative and event), and subsequently, the membership function can be obtained by further analyzing all decision-makers' opinions.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the risk of swelling of rock had the highest rank [26]. Sun et al [27] investigated tunnel collapse risk using multistate fuzzy Bayesian networks. The results showed that this method was very suitable for evaluating of the collapse probability of the Yu Liao Tunnel [27].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [27] investigated tunnel collapse risk using multistate fuzzy Bayesian networks. The results showed that this method was very suitable for evaluating of the collapse probability of the Yu Liao Tunnel [27]. Xiong et al [28] proposed a method for 3D multi-scale geology modeling for tunnel engineering risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian networks can be used to solve the practical problems based on the case [9][10][11][12]. Conditional probability tables have been established by expert investigation with fuzzy Bayesian networks [13][14]. In addition, some assessment methods are applied during the mine gas disaster research process [15][16][17][18].…”
mentioning
confidence: 99%